The effect of substance use during pregnancy on neonatal outcomes in Ethiopia: A systematic review and meta-analysis. Issue 4 (April 2021) - Bayih, Wubet Alebachew; Belay, Demeke Mesfin; Ayalew, Metadel Yibeltal; Tassew, Misganaw Abie; Chanie, Ermias Sisay; Feleke, Dejen Getaneh; Asnakew, Sintayehu; Legas, Getasew; Belete, Amsalu; Mekie, Maru; Yitbarek, Getachew Yideg; Aytenew, Tigabu Munye; et al.
Abstract: Background: Substance use during pregnancy mainly khat chewing (20%) and alcohol drinking (18.1%) are commonly practiced in Ethiopia. However, the effect of using these substances has not been studied nationally yet. Thus, this study was aimed to examine national evidence about the effect of substance use during pregnancy on birth outcome in the country, 2020. Methods: Primary studies were accessed through Google scholar, HINARI, SCOPUS and PubMed databases. The methodological and evidence quality of the included studies were critically appraised by the modified Newcastle-Ottawa quality assessment tool scale adapted for observational studies. From eligible studies, two authors extracted author/year, study region, study design, sample size and reported effect of antenatal substance use on birth outcome on an excel spreadsheet. During critical appraisal and data extraction, disagreements between the two authors were resolved by the involvement of a third author. The extracted data were then exported to stata version 14. Effect sizes were pooled using the fixed-effects model due to homogenous primary studies (I 2 = 0.0%). Presence of publication bias was detected from asymmetry of funnel plot and statistically significant Egger's test (p = 0.000). Results: In this systematic review and meta-analysis, a total of 5, 343 mother-neonate pairs were included from 15 studies. Alcohol, khat, cigarette and narghile were used during pregnancy, and significant adverse birth outcomes attributable to these substances were reported. From the pooled effect of alcohol use, drinking mothers were twice (95%CI: AOR = 2.16; 1.16, 3.17) likely to have newborns with birth defect; 9 times (95% CI: AOR = 9.39; 2.84, 15.94) more prone to own low birth weight neonates; and 1.9 times more prone to deliver preterm neonates (95% CI: AOR = 1.93; 0.52, 3.33) than the nondrinkers. Khat users were 2.4 times (95%CI: AOR = 2.4; 1.11, 5.19) more likely to have congenitally defected neonates; and 3.1 times (95%CI: AOR = 3.19; 1.01, 5.37) more risked to possess low birth weight neonates. Furthermore, antenatal cigarette smokers (95% CI: AOR = 4.36 (1.75, 6.98)) and narghile users (95% CI: AOR = 20.1; 3.94, 103) were at 4 and 20 times more likelihood of having low birth weight neonates as compared to their counterparts. Conclusion: Prematurity, low birth weight and congenital malformation were the investigated adverse effects of antenatal substance use in Ethiopia. Therefore, the existing public health efforts should be encouraged to help women stop using these substances completely before pregnancy. Moreover, increasing public awareness about the potential negative impacts of substance use during pregnancy on birth outcome would be of greatest importance for comprehensive prevention of the problem. Abstract : Ethiopia, Birth outcome, Substance use, Pregnancy, Meta-analysis